Analysis of University Students' Narcissism, Affiliation, Intimacy, and Power Motive - Attiya Khan; Sajid Mahmood Alvi; Zahid Khan (Journal of Management Practices, Humanities and Social Sciences, 2023)
This investigation explores the connections between narcissism, intimacy, affiliation, and power motivation. The information from the individuals was gathered. Using the NPI-16, a test for narcissistic personality, which Cameron P. Anderson, Paul Rose, and Daniel Ames invented it in 2006. The Carl J. Descutner and Thelen (1991) Intimacy Scale having (38 items) and the Unified Motive Scale are based on a joint IRT analysis of 14 existing motive scales that was developed by (Schonbrodt & Gerstenberg, 2012). 300 individuals from various colleges (government and private) and the University of Haripur made up the sample. Data was gathered using the convenience sample method with a door-to-door survey, and the link between the hypotheses and data was evaluated using the t test, Pearson correlation, and independent t test. The study's hypotheses were confirmed. According to current study intimacy has positive correlation with affiliation and power motive and affiliation has also positive correlation with power motive. The results indicate that, in comparison to women, men scored highly on narcissism. By using Pearson correlation method findings indicate that narcissism has non-significant negative relation with power motive. The study's conclusions would be beneficial and encouraging for academics, educators, and counsellors to suggest how to deal with narcissism issues, through which process we increase affiliation and intimacy and how we become more motivated to get power through skills, appreciation and enhance reputation in a positive way and by don’t violating others.